THE EFFECTIVENESS OF USING BOARD RACE GAMES TO ENHANCE STUDENTS’ VOCABULARY MASTERY: (A Pre-experimental Study At Class VIII A of MTs. Salafiyah Syafi’iyah Tebuireng In The Academic Year of 2024/2025) - Ilham Aufa, Muhamad; Zuhriyah , Mukminatus (E-Link Journal, 2024)
A preliminary study conducted at MTS Salafiyah Syafi'iyah Tebuireng provided an in-depth understanding of the challenges faced by students in class VIII-A. One of the challenges identified was the students' difficulty in enriching and expanding their vocabulary using board race game. This research aims to examine whether the board race game can help improve students' vocabulary comprehension at class VIII A of MTs. salafiyah syafi’iyah tebuireng. Using a pre-experimental design, the study was carried out over two treatment sessions. After the treatment, there was a significant improvement in students' vocabulary comprehension based on data analysis with a two-tailed significance value of 0.005 which is lower than the significance threshold of 0.05. These results indicate that the use of the Board Race Game is effective in teaching vocabulary to eighth-grade students in MTs Salafiyah Syafi'iyah Tebuireng during the academic year 2024-2025.